2020
DOI: 10.1590/1519-6984.219529
|View full text |Cite
|
Sign up to set email alerts
|

Fumigant toxicity of some essential oils against Red Flour Beetles, Tribolium castaneum (Herbst) and its safety to mammals

Abstract: Fumigant activities for three essential oils; Garlic oil (Allium sativum L); Chili pepper (Capsicum annuum L.) and Nigella (Nigella sativa L.) were assessed at different concentrations against the adult and 20-days old larval stages of Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae) in the laboratory. The accumulative mortality was observed at different exposure periods (3, 5 and 7 days). The residual effect of garlic oil that was the effective oil, on the treated wheat grains was evaluated with respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The results indicated that the fumigant toxicity of oils and their nanoformulations were positively concentration‐dependent. The coherent effect of oil and nanoformulation concentration on respiratory toxicity against T. castaneum has been demonstrated in various studies 60–62 . Further recordings of T. castaneum mortality in time for nanoformulations indicated that at the concentration of 0.8 μl L −1 air of CSNPs‐loaded GO, 92% and 100% mortalities were achieved at 24 and 72 h exposure time, 63 respectively.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…The results indicated that the fumigant toxicity of oils and their nanoformulations were positively concentration‐dependent. The coherent effect of oil and nanoformulation concentration on respiratory toxicity against T. castaneum has been demonstrated in various studies 60–62 . Further recordings of T. castaneum mortality in time for nanoformulations indicated that at the concentration of 0.8 μl L −1 air of CSNPs‐loaded GO, 92% and 100% mortalities were achieved at 24 and 72 h exposure time, 63 respectively.…”
Section: Resultsmentioning
confidence: 90%
“…The coherent effect of oil and nanoformulation concentration on respiratory toxicity against T. castaneum has been demonstrated in various studies. [60][61][62] Further recordings of T. castaneum mortality in time for nanoformulations indicated that at the concentration of 0.8 μl L À1 air of CSNPs-loaded GO, 92% and 100% mortalities were achieved at 24 and 72 h exposure time, 63 respectively. Similarly, for CSNPs-loaded CO at a concentration of 1 μl L À1 air, 89% and 100% mortalities were obtained at 24 and 72 h exposure time, respectively.…”
Section: Fumigant Toxicitymentioning
confidence: 99%
“…Higher oxygen demand by adult T. castaneum could have led to an increase in absorption of insecticidal compounds though their spiracles. These compounds might have disrupted the normal respiratory activities of the adults more than the larvae, resulting in suffocation and death (Huang et al, 2000;Ogungbite & Oyeniyi, 2014;Sileem et al, 2019).…”
Section: Discussionmentioning
confidence: 99%